Respiratory infection induced episode of alveolar hemorrhage (RIIEAH) in the pediatric diffuse alveolar hemorrhage: a retrospective single-center study - Qing Wei; Xun Chen; Yan Li; Chunyan Li; Xiaobo Zhang; Guangmin Nong; Jing Liu (BMC Pediatrics)
Abstract Background Respiratory infections are recognized as common triggers of alveolar hemorrhage episodes in pediatric diffuse alveolar hemorrhage (DAH). However, comprehensive studies investigating this association in detail remain limited. The aim of this study was to explore the etiological spectrum, clinical features, treatment strategies and outcomes of the respiratory infection induced episode of alveolar hemorrhage (RIIEAH) in the pediatric DAH. Methods The children of DAH who had RIIEAH and a definite etiological diagnosis were included. All the subjects had been hospitalized in the Department of Pediatrics at the First Affiliated Hospital of Guangxi Medical University from January 2023 to February 2024. A retrospective, single-center study was conducted. Results 1. A total of 21 RIIEAHs were included, in which 12 RIIEAHs occurred at the unstable stage, 6 RIIEAHs occurred at the stable stage and 3 RIIEAHs occurred at the end stage. 2. Various pathogens could result in RIIEAHs including mycoplasma pneumoniae (n = 7), coronavirus (n = 3), haemophilus influenzae (n = 3), chlamydia pneumoniae (n = 2), human metapneumovirus (n = 2), acinetobacter baumannii (n = 1), pueumocystis carinii (n = 1) and mixed pathogens (n = 2). 3. The majority of the RIIEAHs (n = 19) presented with prodromal symptoms. Clinical manifestations of RIIEAHs included worsening anemia (n = 13), hemoptysis (n = 13), bleeding on bronchoscopy (n = 12) and dyspnea (n = 9). 4. An intensive glucocorticoid therapy was administrated in the 19 RIIEAHs, in which 18 RIIEAHs resolved. Conclusions RIIEAH can be caused by various pathogens at any disease stage of pediatric DAH and an intensive glucocorticoid therapy seems to be effective for this condition.